5-Methoxyhydnocarpin shows selective anti-cancer effects and induces apoptosis in THP-1 human leukemia cancer cells via mitochondrial disruption, suppression of cell migration and invasion and cell cycle arrest (Bangladesh Journal of Pharmacology, 2016)
The primary objective of the current investigation was to study the anti-tumor effects of 5-methoxyhydnocarpin in THP-1 human leukemia cells along with evaluating its effects on apoptotic induction, cancer cell migration and cell cycle phase distribution. MTT cell viability assay revealed the cell cytotoxic effects while as clonogenic assay revealed the effects of the compound on colony formation tendency. Phase contrast microscopy revealed the effects on cell morphology while as its effects on cell cycle and apoptosis induction were evaluated by flow cytometer. Results showed that 5-methoxyhydnocarpin induced both anchorage-dependent and anchorage-independent cytotoxic effects in THP-1 cells. 5-Methoxyhydnocarpin-treated cells exhibited significant changes in cell morphology. Flow cytometry experiment indicated that 5-methoxyhydnocarpin led to sub-G1 cell cycle arrest and also led to early and late apoptosis.Video Clips of Methodology:38 sec   Click to watch59 sec   Click to watch40 sec   Click to watch4 sec     Click to watch45 sec   Click to watch 16 sec   Click to watch11 sec   Click to watch